Exploratory Analysis of Customer Satisfaction in Case of Cluj-Napoca City Hall Social Canteen - Horia M. RABOCA; Ioan LAZĂR; Adina SOLOMON (Transylvanian Review of Administrative Sciences, 2009)
This study is an exploratory analysis ofcustomers’ satisfaction with regard to the servicesprovided to people on welfare by the socialcanteen organized by Cluj-Napoca City Hall. Inaddition to assessing customers’ satisfaction, italso aims to highlight the main factors influencingthe satisfaction level. The satisfaction modelwas constructed and tested on the results of asurvey conducted among the people benefiting theservices from the institution mentioned.The questionnaire’s structure allows for theassessment of satisfaction construct and role, andpays attention to the influence that quality attributesand client expectations have on satisfaction,revealing that these directly and significantly affectthe level of customers’ satisfaction.Univariate statistical analysis of data andstructural model analysis are used to emphasizethe attributes of the quality of service that affect toa high extent customer satisfaction and that can beused at managerial level to increase service qualityin order to achieve higher customer satisfaction.Also from the managerial point of view, thestudy has a dual significance. It is linked to theconcerns for ensuring and improving the qualityof services in order to increase the customers’satisfaction, as well as to concerns about theimage of the institution.